TINGKAT PENDIDIKAN, KESADARAN WAJIB PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAANBERMOTOR DI KOTA CILEGON BANTEN - Lilik Ambarwati; Lia Narisha Nasution (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to determine the effect of education level, taxpayer awareness, and tax sanctions on motor vehicle taxpayer compliance in Cilegon City, Banten. This research uses primary data with a quantitative method by distributing questionnaires. The population consists of 241,250 registered taxpayers, and the sample was determined using the Slovin formula with purposive sampling, resulting in a sample of 100 motor vehicle taxpayers registered at the Banten Central Bureau of Statistics. The findings indicate that education level, taxpayer awareness, and tax sanctions partially influence motor vehicle taxpayer compliance. Additionally, these three variables simultaneously have a significant effect on taxpayer compliance. Motor vehicle taxpayers in Cilegon City are expected to enhance their awareness and understanding of the importance of paying vehicle taxes on time.